Lead Free Multilayer Piezoelectric Actuators by Economically New Approach - Hussain, Fayaz; Khesro, Amir; Lu, Zhilun; Wang, Ge; Wang, Dawei (Frontiers in Materials, 2020)
The replacement of lead zirconate titanate ceramics (PZTs), with a lead-oxide (PbO)-free alternative is the subject of intense investigation worldwide. In this research, a cheap reliable methodology for the fabrication of multilayers (MLs) of lead-free potassium sodium niobate (KNN)-based ceramics is presented without the need for vacuuming and/or hot isostatic pressing of the tape. The thickness per active layer was 193 μm and 102 μm for the 10 and 16 layer MLs actuators, respectively. Effective d33 (piezoelectric coefficient), effective d33∗ (electrostrain coefficient), bi-polar strain (Smax), max displacement, dielectric constant (ϵr) and loss (tanδ) are 2500 pC/N, 4604 pm/V, 0.17%, 2.2 μm, 1812 and 2% at 1 kHz, respectively, where the effective d33 or d33∗ is the total output of all layers together. The ultimate target materials for potential substitution with KNN-based ceramics and MLs are commercial PZT-4 and PZT-8.